Impact of TNF-α profile in recurrent pregnancy loss pathogenesis: A patient based study from Assam. (November 2021) - Begum, Anjuma; Mishra, Archana; Das, Chandana Ray; Das, Somdatta; Dutta, Ratul; Kashyap, Natasha; Bose, Purabi Deka; Bose, Sujoy
Highlights: The present novel data clearly suggests that the altered site specific differential expression of TNF-α influences RPL predisposition. The TNF-α -308 variant genotype associated with increased serum TNF-α levels is of prognostic significance. TNF-α deregulation resulting in improper immunological regulation may critically influence the Th1/Th2 balance disturbing the tight regulation of feto-maternal interface leading to RPL. The data holds scientific importance and clinical relevance for further studies on association of changes in immune milieu in RPL pathogenesis. TNF-α expression and genotype combinatorially may serve as a useful prognostic biomarker for RPL and used for therapeutic targeting for controlling RPL. Abstract: Background: Lacunae exist in understanding the underlying etiology in majority of recurrent pregnancy loss (RPL) cases. Given the significance of regulated immune-modulation in pregnancy, and the central role of pro-inflammatory TNF-α plays in it; this study targeted to appraise the significance of TNF-α profile in RPL pathogenesis in an ethnically distinct population from Assam, India. Methods: Term delivery, medically terminated pregnancy (MTP) and RPL cases (based on ASRM criteria) were enrolled with no anatomical and chromosomal abnormalities or pathological infections; and blood and/or placenta/product of conceptus (POC) tissue samples were collected with informed consent. Serum level and tissue level TNF-α expression profile were screened using specific molecular tools, and was correlated with TNF-α −308 G/A genotype; for its association with RPL predisposition. Results: A significant gestation specific increase in serum TNF-α levels was observed in MTP cases (19.932 ± 4.407 pg/mL) compared to term delivery subjects (p = 0.001), while a comparable levels were observed with RPL cases (22.709 ± 5.833 pg/mL) (p = 0.646). A site specific (POC) increased expression was observed in RPL compared to MTP cases at both at transcript (6.37 ± 3.714 folds) and protein levels. The TNF-α -308 variant genotype was associated with increased predisposition to RPL (OR = 1.721) compared to MTP as well as significantly increased serum TNF-α levels (p = 0.017); especially in subjects with a homozygous TNF-α -308 A/A genotype. Conclusion: Our data emphasizes on the importance of site specific TNF-α expression levels in RPL pathogenesis in the studied population, and underlines its importance in screening, clinical stratification, and therapeutics by molecular targeting using TNF-α inhibitors.